Impak globalisasi media terhadap kesepaduan sosial dalam kalangan belia di Malaysia - Yaccob, Yasmin; Ibnu, Ireena Nasiha; Alan, Ribka (Journal of Islamic, Social, Economics and Development (JISED), 2023)
Malaysian youth have enjoyed a media-rich environment at the best level. The ability to have entertainment technology is increasing and the rate of internet use among youth is also at a high level. In today's era of Globalization, the youth generation is now increasingly absorbing the culture of the virtual world. Social cohesion is an important essence in strengthening the role of youth in Malaysia. Media is a site of integration in achieving unity. Filling the media and communication is an element in measuring the success of integration. This study aims to provide information and explanations about the use of media as a site of integration and the role of youth in forming social cohesion. This study uses a qualitative approach through non-participant observation and focused discussion groups involving 22 youth and youth leaders in Malaysia. Analysis of the findings of the study found that the media is an agent of change and the best platform for youth to share about the importance of social cohesion. The rapid development of technology in the mass media also affects the behaviour of individuals and society. The concern and moral values in the implementation of activities have formed positive aspects in the behaviour of youth. Therefore, the use of media towards beneficial matters can be used as an indicator in shaping social harmony, especially among the Malaysian society.